Outdoor Air Pollutants and Patient Health - LAUMBACH, ROBERT J. (2010)
Almost 160 million persons live in areas of the United States that exceed federal health-based air pollution standards. The two air pollutants that most commonly exceed standards are ozone and particulate matter. Ozone and particulate matter can harm anyone if levels are sufficiently elevated, but health risk from air pollution is greatest among vulnerable populations. Both ozone and particulate matter can cause pulmonary inflammation, decreased lung function, and exacerbation of asthma and chronic obstructive pulmonary disease. Particulate matter is also strongly associated with increased cardiovascular morbidity and mortality. Children, older adults, and other vulnerable persons may be sensitive to lower levels of air pollution. Persons who are aware of local air pollution levels, reported daily by the U.S. Environmental Protection Agency as the Air Quality Index, can take action to reduce exposure. These actions include simple measures to limit exertion and time spent outdoors when air pollution levels are highest, and to reduce the infiltration of outdoor air pollutants into indoor spaces.